Pandemic Influenza is a Strong Motivator for Participation in Vaccine Clinical Trials among HIV-Positive Canadian Adults. Issue 4 (2009) - Kiberd, MB; Cooper, C; Slaunwhite, JM; Halperin, B; Haase, D; McNeil, SA
Abstract : BACKGROUND: HIV-positive patients represent an immunosuppressed population at risk for severe influenza. In the event of a pandemic, such as 2009 H1N1, rapid implementation of vaccine clinical trials in target populations will be critical. In the present paper, knowledge and attitudes of HIV-positive adults regarding seasonal/pandemic influenza vaccination were evaluated, and facilitators and barriers to participation in vaccine clinical trials were explored. METHODS: A validated, 70-item, self-administered questionnaire was distributed to all HIV patients presenting for routine follow-up at eight Canadian Institutes of Health Research Canadian HIV Trials Network (CTN) sites from October 2008 to February 2009, as well as all participants in CTN trial 237. This study has representation from all Canadian provinces. RESULTS: In total, 610 HIV-positive adults responded (298 CTN 237 participants; 312 non-CTN 237 participants). Most reported receiving influenza vaccine last season (83% of CTN 237 participants versus 83% non-CTN 237 participants; P not significant) and most would receive a pandemic influenza vaccine if offered (76% versus 73%; P not significant). A majority believed that it was important to include HIV patients in vaccine clinical trials (65% versus 53%; P<0.001) and would agree to participate in trials of a pandemic vaccine if invited (86% versus 51%; P≤0.0001). Predictors of willingness to participate in a pandemic vaccine trial were 'desire to be protected from pandemic flu', OR 4.5 (95% CI 2 to 8) and 'desire to help others', OR 2.3 (95% CI 1.3 to 4.5). 'Fear of needles', OR 0.49 (95% CI 0.1 to 1.5) and 'need for extra blood tests', OR 0.49 (95% CI 0.2 to 1.4) were key barriers to participation. CONCLUSION: Most HIV-positive Canadian adults surveyed receive influenza vaccination. Protection from pandemic influenza is considered important and is a motivator for receiving influenza vaccine and future trial participation. Modifiable barriers to these objectives identified in the present study should be the focus of efforts to increase influenza immunization in this population.